Endoscopic submucosal dissection for early rectal neoplasia: experience from a European center - Probst, Andreas; Ebigbo, Alanna; Märkl, Bruno; Schaller, Tina; Anthuber, Matthias; Fleischmann, Carola; Messmann, Helmut (Endoscopy, 2017)
Background and study aims Endoscopic resection is a curative treatment option for large nonpedunculated colorectal polyps (LNPCPs). Endoscopic submucosal dissection (ESD) allows en bloc resection but ESD experience is still limited outside Asia. The aim of our study was to evaluate the role of ESD in the treatment of early rectal neoplasia in a European center.Patients and methods 330 patients referred for endoscopic resection of rectal LNPCPs were included prospectively.Results ESD was performed for 302 LNPCPs (median diameter 40 mm). Submucosal invasive cancer (SMIC) was present in 17.2 % (n = 52). SMIC was associated with Paris type (54.5 % among type 0-Is lesions, 100 % of 0-Is-IIc type, 0 % of 0-IIa, 14.9 % of 0-IIa-Is, and 59.3 % of 0-IIa-IIc type; P < 0.001) and with surface pattern (71.4 % among nongranular plus mixed surface lesions, 17.9 % of lesions with granular surface and nodule ≥ 10 mm). For SMICs, resection rates were en bloc 81.4 %, R0 65.1 %, and curative 30.2 %. Curative resection rate improved from 13.6 % to 47.6 % over the study period (P = 0.036). The reason for 83.3 % (25/30) of noncurative resections was submucosal invasion exceeding 1000 µm. For benign lesions (n = 250, 82.8 %), the R0 resection increased from 55.2 % to 84.8 % over the study period (P < 0.001). Recurrence rate was 4.8 %, bleeding rate 5.2 %, and perforation rate 0.8 % (all complications managed conservatively). Median follow-up was 35 months.Conclusions The majority of rectal LNPCPs are benign lesions. ESD offers high R0 resection and low recurrence rates but EMR may be appropriate. In lesions with a risk for SMIC, ESD should be offered to achieve R0 resection. Despite high rates of R0 resection the curative resection rate of ESD for rectal SMIC is < 50 %. Pretherapeutic lesion selection needs improvement.